2017
DOI: 10.1093/bioinformatics/btx178
|View full text |Cite
|
Sign up to set email alerts
|

Spresso: an ultrafast compound pre-screening method based on compound decomposition

Abstract: MotivationRecently, the number of available protein tertiary structures and compounds has increased. However, structure-based virtual screening is computationally expensive owing to docking simulations. Thus, methods that filter out obviously unnecessary compounds prior to computationally expensive docking simulations have been proposed. However, the calculation speed of these methods is not fast enough to evaluate ≥ 10 million compounds.ResultsIn this article, we propose a novel, docking-based pre-screening p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…To achieve these requirements, we first decomposed 1,615 FDA-approved drug structures obtained from the ZINC database 20 on 11 April 2019 with a modified Spresso decomposition algorithm 21 that cleaves rotatable bonds to generate rigid substructures. There is only one modification from the original decomposition method that does not increase a hydrogen-bond donor atom: the cleaved site is methylated if it is a hetero atom, and a hydrogen atom is added otherwise.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…To achieve these requirements, we first decomposed 1,615 FDA-approved drug structures obtained from the ZINC database 20 on 11 April 2019 with a modified Spresso decomposition algorithm 21 that cleaves rotatable bonds to generate rigid substructures. There is only one modification from the original decomposition method that does not increase a hydrogen-bond donor atom: the cleaved site is methylated if it is a hetero atom, and a hydrogen atom is added otherwise.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Recently, fragment-based drug discovery (FBDD) has attracted much attention in the field of drug discovery. The method evaluates a drug candidate compound by the combination of fragments of the compound [15,24,25]. The number of unique fragments included is rather saturating, even when the size of the compound database grows very rapidly [24].…”
Section: Possibility Of Application For Drug Discoverymentioning
confidence: 99%
“…The method evaluates a drug candidate compound by the combination of fragments of the compound [15,24,25]. The number of unique fragments included is rather saturating, even when the size of the compound database grows very rapidly [24]. Considering this context, several methods have been proposed for solving the problems appearing in the FBDD as combinatorial optimization problems.…”
Section: Possibility Of Application For Drug Discoverymentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this limitation, computational approaches that use ligand docking scores as approximations of experimental data have been suggested. Recently, virtual screening [ 13 , 14 , 15 , 16 , 17 ] algorithms combining ML algorithms with docking scores have been suggested. Gentile et al [ 13 ] suggested a deep-docking approach that uses a docking score prediction model to reduce the resources required for docking computations.…”
Section: Introductionmentioning
confidence: 99%